Effect of Huaier on the proliferation and apoptosis of human gastric cancer cells through modulation of the PI3K/AKT signaling pathway - XIE, HUA-XIA (Exp Ther Med, 2015)
The aim of the present study was to investigate the effect of Huaier on the proliferation and apoptosis of the MKN45 and SGC7901 gastric cancer cell lines. The MTT assay was used to measure the effects of Huaier on the growth of the cells, while cell cycle distribution and apoptosis levels were analyzed using flow cytometry. Western blotting was used to assess the levels of proteins associated with the apoptotic pathway. It was found that cell survival decreased with the increase in the concentration of Huaier, and the apoptosis rates were increased in a dose-dependent manner both in MKN45 and SGC7901 cells. The number of cells in the G2/M phase in the Huaier-treated groups was increased in a dose-dependent manner compared with that in the control group. Huaier inhibited phosphorylated- (p-)AKT1, phosphatidylinositol 3-kinase (PI3K), pyruvate dehydrogenase kinase isoform 1, p-phosphatidylinositol 3,4,5-trisphosphate 3-phosphatase and dual-specificity protein phosphatase and B-cell lymphoma 2 expression and upregulated cleaved-caspase-9 expression in a dose-dependent manner. In conclusion, Huaier can strongly inhibit gastric cancer cell proliferation by inhibiting cyclin B1 expression, promoting G2/M-phase arrest and modulating the PI3K/AKT signaling pathway, and can induce gastric cancer cell apoptosis by modulating the PI3K/AKT signaling pathway in dose-dependent manner.